1989
DOI: 10.1093/geronj/44.2.p45
|View full text |Cite
|
Sign up to set email alerts
|

Data Quality and Age: Health and Psychobehavioral Correlates of Item Nonresponse and Inconsistent Responses

Abstract: This study examined item nonresponse and inconsistent responses (IRs) and their health and psychobehavioral correlates in a population-based survey of adults 65 years and older. We administered an in-person questionnaire concerning physical, social, and psychological health to 1,155 men (mean age = 73.7 years) and 1,942 women (mean age = 74.8 years). Nonresponse rates varied with item topic, and "don't know" (DK) responses were more common than refusals. DKs increased with age of respondent, tended to be more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 0 publications
8
58
1
1
Order By: Relevance
“…Several studies have found higher rates of item nonresponse to health surveys among those with poor health, cognitive impairment, or physical impairment (e.g., Colsher and Wallace 1989;Guadagnoli and Cleary 1992). Whereas Colsher and Wallace (1989) found respondent age independently associated with item nonresponse rate among the community-dwelling elderly and Sherbourne and Meredith (1992) found a similar increase in item nonresponse among patients with chronic conditions, Guadagnoli and Cleary (1992) found no independent effect of age among recently discharged surgical patients.…”
Section: Item Nonresponsementioning
confidence: 99%
“…Several studies have found higher rates of item nonresponse to health surveys among those with poor health, cognitive impairment, or physical impairment (e.g., Colsher and Wallace 1989;Guadagnoli and Cleary 1992). Whereas Colsher and Wallace (1989) found respondent age independently associated with item nonresponse rate among the community-dwelling elderly and Sherbourne and Meredith (1992) found a similar increase in item nonresponse among patients with chronic conditions, Guadagnoli and Cleary (1992) found no independent effect of age among recently discharged surgical patients.…”
Section: Item Nonresponsementioning
confidence: 99%
“…For example, there may be altered recall of historical risk factors or prior medical conditions with increasing age, in addition to the longer period of time that is to be recalled. Measured cognitive function has been related to reliability of responses in questionnaire studies of older persons (9). For various reasons, there may be more difficulty with understanding various kinds of questionnaires, computeraided assessment devices, or other data collection modalities.…”
Section: Respondent Characteristicsmentioning
confidence: 99%
“…Firstly, prevalence of PD increases with age, increasing from 0.6% in persons aged 65-69 to 2.6% in those aged 70-80 years 5 . Declining data quality with increasing age has been observed in self-report data from research involving general populations 6 . Secondly, the onset of PD is a slow and insidious process commencing some time prior to development of noticeable motor symptoms 7,26,27 .…”
Section: Introductionmentioning
confidence: 99%